Monocarboxylate transporter and lactate metabolism - Kitaoka, Y.; Hoshino, D.; Hatta, H. (The Journal of Physical Fitness and Sports Medicine, 2012)
For many years, lactate was considered as a metabolic waste product, and a cause of fatigue during exercise. However, lactate is now known as a carbohydrate fuel source, shuttled between cells and tissues. The movement of lactate across the plasma membrane is facilitated by a family of monocarboxylate transporters (MCTs). Among 14 identified MCT isoforms, MCT1 and MCT4 are present in the plasma membranes of skeletal muscle and are suggested to be related to exercise performance. Reports have shown that exercise training increases both MCT1 and MCT4 in skeletal muscle. This review will discuss the role of lactate as a fuel and exercise training-induced changes in lactate metabolism. In addition, studies of Thoroughbred horses, as models of elite athletes, are introduced.